2015
DOI: 10.1038/ncomms6963
|View full text |Cite
|
Sign up to set email alerts
|

Sub-50-nm self-assembled nanotextures for enhanced broadband antireflection in silicon solar cells

Abstract: Materials providing broadband light antireflection have applications as highly transparent window coatings, military camouflage, and coatings for efficiently coupling light into solar cells and out of light-emitting diodes. In this work, densely packed silicon nanotextures with feature sizes smaller than 50 nm enhance the broadband antireflection compared with that predicted by their geometry alone. A significant fraction of the nanotexture volume comprises a surface layer whose optical properties differ subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
189
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(197 citation statements)
references
References 33 publications
5
189
0
Order By: Relevance
“…The pitch of the array was 450 nm. The last shape was a combination of a cone and a sphere, which was recently realized by polymer self-assembly [13]. The dimensions and pitch of this array were exactly the same as those of the first one (i.e.…”
Section: Simulationmentioning
confidence: 66%
“…The pitch of the array was 450 nm. The last shape was a combination of a cone and a sphere, which was recently realized by polymer self-assembly [13]. The dimensions and pitch of this array were exactly the same as those of the first one (i.e.…”
Section: Simulationmentioning
confidence: 66%
“…We use black silicon [13,14,11] nanostructuring to achieve low reflectance, which can be modelled in a mean-field approximation as a graded refractive 10 index at the Si-air interface [15]. von Gastrow et al [16] reported excellent passivation of black Si surfaces using atomic layer deposition (ALD) of Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the typical front surface reflectance of ∌ 2 and ∌ 8 %, from conventionally textured mono- [8] 5 and multi-crystalline [9] Si solar cells, respectively, nanoscale texturing such as described in [10,11,12] offers a potential of improved power conversion efficiency for Si solar cells due to reduced reflectance loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nanostructured graded-index AR coatings are the most promising ones with respect to polarization insensitivity, broad-band and omnidirectional antireflectivity properties required for a perfect antireflective performance [9][10][11][12][13][14]. In these materials the optical impedance matching and, therefore, effective suppression of the reflection occurring on the surface, can be implemented via tapered index design, where the ordered array of tapered pillars acts as a layer for the gradually changing refractive indexes.…”
Section: Introductionmentioning
confidence: 99%